Is There any Correlation Between Pathological Profile of Facet Joints and Clinical Feature in Patients With Thoracolumbar Kyphosis Secondary to Ankylosing Spondylitis?: An Immunohistochemical Investigation. Issue 9 (May 2016) - Qian, Bang-ping; Ji, Ming-liang; Qiu, Yong; Pan, Tao; Wang, Bin; Mao, Sai-hu; Jiang, Jun; Shi, Wei; Luo, Yong-feng
Abstract : Study Design: An immunohistochemical analysis. Objective: The aim of this study was to systematically and extensively evaluate the immunopathology of the facet joints in patients with thoracolumbar kyphosis secondary to ankylosing spondylitis (AS). Summary of Background Data: The facet joints may be predominantly involved in the process of spinal inflammation in AS. Thus, a detailed investigation of the immunopathology at sites of facet joints is of crucial importance in understanding the pathogenesis of AS. Methods: The facet joints were obtained from 30 AS patients and 23 age- and gender-matched controls (patients with fresh thoracolumbar fracture). The facet joints were assessed immunohistochemically by analyzing the number of infiltrating T cells (CD3, CD4, CD8), B cells (CD20), microvessel density (CD34), osteoblasts (CD56), bone marrow macrophages (CD68), and osteoclasts (CD68) per high-power field (hpf). According to the presence or absence of persistent inflammation, AS patients were divided into 2 groups: A (patients with persistent inflammation) and B (patients without persistent inflammation). Lumbar spinal mobility was assessed using the modified Schober index (MSI). Results: Two or more CD3+ T cell aggregates were found in the facet joints from 18 of 30 AS patients, whereas 1 CD3+ T cell aggregate was noted in 5 of 23 patients with thoracolumbar fracture. The levels of T cells (CD4+ and CD8+), CD20+B cells, CD56+ osteoblasts, and CD34+ microvessel density were significantly higher in AS patients than in the controls (all P  < 0.01). Notably, the MSI score in group A was significantly higher than that in group B ( P  < 0.01). Conclusion: Active spinal inflammation is frequently observed in AS patients with thoracolumbar kyphosis. In addition, persistent inflammation in facet joints may further contribute to the loss of spinal mobility in the later stages of AS. These findings indicate that careful monitoring of disease activity is mandatory for AS patients in its advanced stage. Level of Evidence: 4